Intravenous Thrombolysis in Patients with Acute Ischemic Stroke after a Reversal of Dabigatran Anticoagulation with Idarucizumab: A Real-World Clinical Experience - Šaňák, Daniel; Jakubíček, Stanislava; Černík, David; Herzig, Roman; Kunáš, Zdeněk; Mikulík, Robert; Ostrý, Svatopluk; Reif, Michal; Rohan, Vladimír; Tomek, Aleš; Veverka, Tomáš (Journal of stroke and cerebrovascular diseases, 2018)
BACKGROUND: Intravenous thrombolysis (IVT) is contraindicated in patients with acute ischemic stroke (AIS) using oral anticoagulants. A specific human monoclonal antibody was introduced to reverse immediately the anticoagulation effect of the direct inhibitor of thrombin, dabigatran. Until now, mostly individual cases presenting with successful IVT after a reversal of dabigatran anticoagulation in patients with AIS were published. Thus, we aimed to report real-world data from clinical practice. METHODS: Patients with AIS on dabigatran treated with IVT after antidote reversal were enrolled in the retrospective nationwide study. Neurological deficit was scored using the National Institutes of Health Stroke Scale (NIHSS) and 90-day clinical outcome using modified Rankin scale (mRS) with a score 0-2 for a good outcome. Intracerebral hemorrhage (ICH) was defined as a presence of any sign of bleeding on control imaging after IVT, and symptomatic intracerebral hemorrhage (SICH) was assessed according to the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST) criteria. RESULTS: In total, 13 patients (7 men, mean age 70.0 ± 9.1 years) with a median NIHSS admission score of 7 points were analyzed. Of these patients, 61.5% used 2 × 150 mg of dabigatran daily. Antidote was administrated 427 ± 235 minutes after the last intake of dabigatran, with a mean activated prothrombin time of 38.1 ± 27.8 seconds and a mean thrombin time of 72.2 ± 56.1 seconds. Of the 13 patients, 2 had ICH and 1 had SICH, and no other bleeding complications were observed after IVT. Of the total number of patients, 76.9% had a good 3-month clinical outcome and 3 patients (23.1%) died. Recurrent ischemic stroke occurred in 2 patients (15.4%). CONCLUSION: The data presented in the study support the safety and efficacy of IVT after the reversal of the anticoagulation effect of dabigatran with antidote in a real-world clinical practice.
Keywords: trombolytická terapie; fibrinolytika; výsledek terapie; Recombinant Proteins; Male; cerebrální krvácení; antidota; retrospektivní studie; intravenózní podání; antikoagulancia; Fibrinolytic Agents; cévní mozková příhoda; Dabigatran; Stroke; Aged; mužské pohlaví; senioři; ischemie mozku; dabigatran; Thrombolytic Therapy; Tissue Plasminogen Activator; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; rekombinantní proteiny; tkáňový aktivátor plazminogenu; Antidotes; lidé; ženské pohlaví; Anticoagulants; Humans; Cerebral Hemorrhage; Retrospective Studies; Administration, Intravenous; Female; Brain Ischemia